A Review of Lumbar Spinal Stenosis with Intermittent Neurogenic Claudication: Disease and Diagnosis. Issue 2 (6th December 2019) - Deer, Timothy; Sayed, Dawood; Michels, John; Josephson, Youssef; Li, Sean; Calodney, Aaron K
Abstract: Objective: Lumbar spinal stenosis (LSS) is a degenerative spinal condition affecting nearly 50% of patients presenting with lower back pain. The goal of this review is to present and summarize the current data on how LSS presents in various populations, how it is diagnosed, and current therapeutic strategies. Properly understanding the prevalence, presentation, and treatment options for individuals suffering from LSS is critical to providing patients the best possible care. Results: The occurrence of LSS is associated with advanced age. In elderly patients, LSS can be challenging to identify due to the wide variety of presentation subtleties and common comorbidities such as degenerative disc disease. Recent developments in imaging techniques can be useful in accurately identifying the precise location of the spinal compression. Treatment options can range from conservative to surgical, with the latter being reserved for when patients have neurological compromise or conservative measures have failed. Once warranted, there are several surgical techniques at the physician's disposal to best treat each individual case.